Implication of ultrasonic power and frequency for the ultrasonic vacuum drying of honey. Issue 10 (12th July 2021) - Jiang, Mengmeng; Bai, Xiting; Sun, Jun; Zhu, Wenxue
Abstract: To determine the best combination of parameters for honey drying with ultrasonic vacuum drying technology, this study evaluated the effect of ultrasonic power and frequency on the drying kinetics of honey. Three ultrasonic frequencies and two ultrasonic powers were chosen to investigate the influence on water transport, storage stability and microstructural changes during ultrasonic vacuum drying. Among all the conditions studied, 40 kHz 80 W was found to be the best with fastest drying rate and shortest drying time. Through the low-field nuclear magnetic resonance analysis, the ultrasonic vacuum drying of honey could effectively remove bound water at 40 kHz frequency coupled with high ultrasonic power. Ultrasonic power and frequency played a positive role in accelerating the mass transfer process. Meanwhile, the honey powder dried at 28 kHz 40 W had the best storability with the highest glass transition temperature ( Tg ) value measured by differential scanning calorimetric. According to the changing trend of Tg, the average molecular weight of carbohydrate in honey was altered due to the impact of different ultrasonic power and frequency, especially at 40 kHz 80 W. The effects on mass transfer properties were confirmed with microstructural observations using scanning electron microscopy. The new findings on the impact of power and frequency on ultrasonic vacuum drying can be potentially beneficial for future food processing development.